Osteoarthritis and multimorbidity in male retired professional footballers compared to men in the general population - Shuaib, Monirah Ali (2025)
Background: Football is one of the most popular sports world-wide. Professional footballers are at higher risk of injuries of lower limb joints and the head due to the nature of the game. This can lead to short- and long-term health consequences such as osteoarthritis (OA) and cognitive disorders. However, whether footballers are at higher risk of developing knee pain, multimorbidity and OA of the foot/ankle after retirement remains unknown.